EXPLORING THE POTENTIAL OF BLOCK CHAIN AND AI CONVERGENCE TO SECURE AND VERIFY IOT DATA TRANSMISSIONS IN HIGH-STAKES INDUSTRIES LIKE HEALTHCARE AND FINANCE - Muhammad Ismail,; Azeem Akram,; Ishteeaq Naeem,; Umair Saleem,; Dr Khawaja Tahir Mehmood,; Raza Iqbal, (Spectrum of Engineering Sciences, 2025)
This paper evaluates Block chain technology and Generative AI solutions for healthcare alongside their healthcare implementation challenges and solution methods. Block chain technology strengthens electronic health record security alongside privacy protection and stands as a solution for improving record interconnection. Smart contracts simultaneously modernize supply chain process management and administrative functions. Block chain technology proves able to authenticate IoT data while protecting its security thus delivering improved medical services through documented case examples. The healthcare industry experienced major transformation through ChatGPT Generative AI which now enables doctors to deliver personalized treatment along with diagnostic tests and predictive outcomes. AI systems process large datasets which helps medical staff diagnose diseases earlier while simultaneously generating treatments personalized for each patient. The implementation of AI-based virtual healthcare assistants has raised patient involvement through real-time information services and better treatment following procedures coupled with continuous user assistance. Generative AI has accelerated medical research along with drug development processes which shortens the duration and decreases expenses involved in medication production. Implementations of Generative AI alongside Block chain systems enable protected patient data storage methods as well as advanced AI training resources and streamlined health operation methods. The existing challenges revolve around scalability and energy consumption together with interoperability issues. The paper creates plans for expandable block chain systems along with controlled information exchange protocols. Medical research together with treatment benefits from these technologies since they improve both safety measures and targeted treatment approaches.